Dysfunctional Uterine Bleeding - Casper, Robert F. (1983)
Dysfunctional uterine bleeding is most commonly associated with chronic anovulation. Early diagnosis of anovulation is important; the induction of regular withdrawal periods using a progestin such as Provera prevents the development of endometrial hyperplasia with the subsequent inevitable occurrence of a heavy, frightening vaginal bleed. The etiology of dysfunctional uterine bleeding occurring during ovulatory cycles is unknown and all medical therapies at present are necessarily experimental. Hysterectomy is probably the treatment of choice for women who have finished their childbearing career and in whom persisting menorrhagia during ovulatory cycles results in anemia.